Mitochondrial targeting overcomes ABCA1-dependent resistance of lung carcinoma to α-tocopheryl succinate - Prochazka, Lubomir; Koudelka, Stepan; Dong, Lan-Feng; Stursa, Jan; Goodwin, Jacob; Neca, Jiri; Slavik, Josef; Ciganek, Miroslav; Masek, Josef; Kluckova, Katarina; Nguyen, Maria; Turanek, Jaroslav; et al. (Apoptosis, 2013)
α-Tocopheryl succinate (α-TOS) is a promising anti-cancer agent due to its selectivity for cancer cells. It is important to understand whether long-term exposure of tumour cells to the agent will render them resistant to the treatment. Exposure of the non-small cell lung carcinoma H1299 cells to escalating doses of α-TOS made them resistant to the agent due to the upregulation of the ABCA1 protein, which caused its efflux. Full susceptibility of the cells to α-TOS was restored by knocking down the ABCA1 protein. Similar resistance including ABCA1 gene upregulation was observed in the A549 lung cancer cells exposed to α-TOS. The resistance of the cells to α-TOS was overcome by its mitochondrially targeted analogue, MitoVES, that is taken up on the basis of the membrane potential, bypassing the enhanced expression of the ABCA1 protein. The in vitro results were replicated in mouse models of tumours derived from parental and resistant H1299 cells. We conclude that long-term exposure of cancer cells to α-TOS causes their resistance to the drug, which can be overcome by its mitochondrially targeted counterpart. This finding should be taken into consideration when planning clinical trials with vitamin E analogues.
Keywords: protinádorové látky; Gene Knockdown Techniques; myši; Mice; ABCA1 protein; Carcinoma, Non-Small-Cell Lung; Animals; nemalobuněčný karcinom plic; ATP-Binding Cassette Transporters; chemorezistence; nádorové buněčné linie; zvířata; alfa-tokoferol; Mitochondria; alpha-Tocopherol; Antineoplastic Agents; mitochondrie; ABC transportéry; Drug Resistance, Neoplasm; nádory plic; Lung Neoplasms; genový knockdown; Cell Line, Tumor; ATP Binding Cassette Transporter 1